Single Umbilical Artery Detected on First-Trimester Ultrasound - Irsa Shuaib, Naheed Khan, Mehmood Akhtar Khattak, Kanwal Rehana, Hina Gul, Kalsoom Nawab (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our research sought to evaluate the utility of a first-trimester ultrasonography diagnostic of a single umbilical artery as a possible indicator of chromosomal abnormalities. Study Design: Retrospective Study Place and Duration: Department of Radiology, Khyber Teaching Hospital Peshawar for the duration from January 2021 to March 2022. Methods: There were 68 pregnant females were of first trimester were presented in this study. Age of the patients was between 18-40 years. After getting informed written consent detailed demographics of enrolled females were recorded. Ultrasound was taken to diagnose single umbilical artery among all cases. SPSS 24.0 was used to analyze all data. Results: Among all, 25 (36.8%) females were aged 18-25 years, 36 (52.9%) cases had age 26-35years and 17 (25%) females had age >35 years. 37 (54.4%) patients had BMI <25kg/m2 and 31 (45.6%) had BMI >25kg/m2. 30 (44.1%) cases were primigravida and 38 (55.9%) cases were multigravida. 40 (58.8%) cases were from rural areas and 33 (48.5%) cases were literate. Overall frequency of single umbilical artery (SUA) was 3 (4.4%) in which 1 (1.5%) in single pregnancy and 2 (2.9%) in twin pregnancy. The first trimester finding had 85% sensitivity, a 97% specificity, a 0.4% false positive rate, and a 14.9% false negative rate. Frequency of malformations was 13 (19.1%). Most cases of severe foetal deformity were detected using ultrasonography in the 16th week. Conclusion: Based on the results of this study, we can say that SUA is a valuable marker for foetal malformation pathology in the first trimester, allowing for the early detection of many instances of malformations before 20 weeks of gestation. Keywords: Ultrasonography, Pregnant Females, First Trimester, Single Umbilical Artery